Sistem Informasi Paket Wisata Sebagai Media Promosi Dan Reservasi Studi Kasus Pada Reyhan Tour - Alfiyatullathifah, Ismi; , Husni Thamrin, S.T., M.T., Ph.D (2016)
Travel agency at this time has a lot of growing, a lot of people in entrepreneurship by opening a company providing travel services. Reyhan Tour is one of the companies engaged in providing travel services or travel agents are known to operate in Kudus, Jepara, Semarang and Solo Raya. Booking travel packages are applied to Reyhan Tour still use the conventional way is to come straight to the company's customers or vice versa, so that in this way it is less effective in the promotion of travel packages offered by Reyhan Tour. This web-based booking system created in order to facilitate the public to know about the package - a travel package offered Reyhan Tour online, so make it easier for current customers wishing to book or inquire about the information package that has not been understood. This website is built using PHP and MySQL CI. The method used in this research is the waterfall method. Steps being taken in this research is to conduct a needs analysis, system design, implementation, system testing, and maintenance. Websites built in addition to being a media campaign as well as a medium for direct booking online. Testing. Based on the results of the questionnaire showed that 82% of 20 respondents said that the system is made useful.